Massive Color-Octet Bosons: Bounds on Effects in Top-Quark Pair Production - Haisch, U; Westhoff, S (2011)
A critical survey of the existing direct and indirect constraints on massive spin-one color octets is presented. Since such new degrees of freedom appear in any extension of the color gauge group to a product of at least two SU(3) factors, we keep our discussion as independent as possible from the underlying theory. In the framework of scenarios that involve flavor non-universal couplings, we show that excessive flavor-changing neutral currents can be avoided by a suitable alignment in flavor space. Constraints from electroweak precision observables and direct production at hadron colliders still leave space for sizable new-physics effects in top-quark pair production, in particular a large forward-backward asymmetry. In this context, we derive a model-independent upper bound on the asymmetry that applies whenever top-antitop production receives the dominant corrections from s-channel exchange of a new single color-octet resonance.